Efficacy of house dust mite sublingual tablet in the treatment of allergic rhinoconjunctivitis: A randomized trial in a pediatric population. Issue 1 (25th November 2018) - Okamoto, Yoshitaka; Fujieda, Shigeharu; Okano, Mitsuhiro; Hida, Hideaki; Kakudo, Shinji; Masuyama, Keisuke
Abstract: Background: The efficacy and safety of 300 index of reactivity (IR) tablets of house dust mite (HDM) allergen extracts in Japanese pediatric (5‐16 years old) patients with allergic rhinitis (AR) were assessed in a double‐blind, randomized, placebo‐controlled study (JAPIC CTI‐152981). Methods: Patients were randomized 1:1 to HDM sublingual tablets or placebo once daily for 52 weeks. The primary end‐point was average adjusted symptom score (AASS; average of daily Rhinitis Total Symptom Scores, comprising sneezing, rhinorrhea, nasal congestion, and nasal pruritus, adjusted for rescue medication use), analyzed during Weeks 48‐52 (mixed‐effects model for repeated measures). Results: Of 438 patients randomized, 403 (92%; 193 active, 210 placebo) completed the study. AASS (least‐squares [LS] mean [SE]) during Weeks 48‐52 was significantly ( P  = 0.0005) lower in the active group compared with placebo (6.32 [0.20] vs 7.27 [0.19]; relative LS mean difference, −13%). Immunological responses (IgE and IgG4 antibodies specific to antigens of two HDM species) were significantly greater in the active group compared with placebo ( P  < 0.0001). Almost all patients experienced mild or moderate adverse events (AEs). The most common treatment‐related AEs were oral pruritus, mouth edema, throat irritation, and ear pruritus. One patient experienced serious pseudocroup (subglottic laryngitis) that recovered. There were no deaths or anaphylaxis requiring the use of injectable adrenaline. Conclusions: The HDM tablet significantly improved symptoms of HDM‐induced perennial AR and was associated with a significant immunological response. The safety profile in pediatric patients was consistent with that in adults, with no new safety concerns.